The politically incorrect guide to communism - Kengor, Paul, 1966- (Politically incorrect guide., 2017)
A brand-new installment of the beloved Politically Incorrect Guide series! The Politically Incorrect Guide to Communism is a fearless critique of freedom's greatest ideological adversary, past and present.